Assessing entrepreneurial self-efficacy among senior high school students: A preliminary study - Eli Hendrik Sanjaya; Deni Ainur Rokhim; Ananta Ardyansyah; Ratna Kumala Dewi; Hayuni Retno Widarti; Munzil Munzil; Muntholib Muntholib; Yahmin Yahmin (Jurnal Pendidikan Ekonomi (JUPE), 2025)
Entrepreneurship is increasingly recognized as an essential skill for students to face global economic and social challenges. However, research on entrepreneurial self-efficacy (ESE) among high school students in Indonesia remains limited, despite its crucial role in shaping entrepreneurial intentions and readiness. This study aims to explore students’ levels of ESE and analyze the influence of gender and entrepreneurial experience on their abilities and intentions. Using a mixed-methods approach, data were collected through surveys measuring knowledge, interest, experience, and ESE. The findings reveal that students have high levels of entrepreneurial knowledge and interest, with ESE ranging from moderate to high. Gender was found to influence knowledge, interest, and ESE, with female students tending to demonstrate stronger entrepreneurial intentions. Moreover, prior entrepreneurial experience was shown to enhance both ESE and students’ interest in entrepreneurship. Qualitative analysis highlighted that students perceive capital, marketing, and product development as key needs for entrepreneurship, while common challenges include competition and financial constraints. Overall, students expressed neutral to positive sentiments toward entrepreneurial engagement. These findings underscore the importance of practical, gender-sensitive, and experiential entrepreneurship education to strengthen ESE and better prepare students for the challenges of the business world.